2007
DOI: 10.1111/j.1464-5491.2007.02096.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of immune mediators at diagnosis of Type 1 diabetes with later clinical remission

Abstract: We conclude that the systemic immunoregulatory state at diagnosis of T1D is predictive of clinical improvement during the remission phase. There was no general change in systemic immune reactivity in the months after diagnosis and initiation of insulin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 49 publications
8
39
2
1
Order By: Relevance
“…In contrast, CCL3 remained stable during follow up suggestive of differential regulation of CCR5 ligands early after diagnosis of type 1 diabetes without general up regulation of systemic immune mediators confirming a previous study [17]. Although these observations suggest a change of cytokines overtime, it is unclear whether this is of clinical or biological meaning.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, CCL3 remained stable during follow up suggestive of differential regulation of CCR5 ligands early after diagnosis of type 1 diabetes without general up regulation of systemic immune mediators confirming a previous study [17]. Although these observations suggest a change of cytokines overtime, it is unclear whether this is of clinical or biological meaning.…”
Section: Discussionsupporting
confidence: 83%
“…First, a more classical definition of partial remission was applied with HbA1c b 7.5% and daily insulin b0.4U/kg (remission 7.5) [17]. However, partial remission discriminated by HbA1c b 7.5% is not always indicative for a euglycemic status.…”
Section: Metabolic Parametersmentioning
confidence: 99%
“…This could not be documented so far in patients with T1D (50). In an experimental approach, such as the one used in the IDDM rat in the present and in previous studies for mono-and combination therapies (25,36), pancreatic tissue could be directly accessed for b-cell analyses by biopsies.…”
Section: Cytokine Profile Changes As Biomarkers For Success Of Combinmentioning
confidence: 98%
“…The techniques for measuring immune mediators in the circulation have improved over the last decade, enabling more detailed and comprehensive investigations than in previous years. Recent studies performed in childhood or adolescent type 1 diabetes have found associations of certain cytokines such as IL-1 receptor antagonist (IL-1 ra), IL-6 and TNF alpha with the presence of type 1 diabetes [7,8] and IL-1 ra, IL-10 and IFN gamma with progression [9,10] of type 1 diabetes; however results are partly discordant. One reason for discrepancies may be unaccounted differences in insulin sensitivity.…”
Section: Introductionmentioning
confidence: 94%